Modeling trauma in rats: Similarities to humans and potential pitfalls to consider - Weber, Birte; Lackner, Ina; Haffner-Luntzer, Melanie; Palmer, Annette; Pressmar, Jochen; Scharffetter-Kochanek, Karin; Knoell, Bernd; Schrezenemeier, Hubert; Relja, Borna; Kalbitz, Miriam (Journal of Translational Medicine, 2019)
Trauma is the leading cause of mortality in humans below the age of 40. Patients injured by accidents frequently suffer severe multiple trauma, which is life-threatening and leads to death in many cases. In multiply injured patients, thoracic trauma constitutes the third most common cause of mortality after abdominal injury and head trauma. Furthermore, 40-50% of all trauma-related deaths within the first 48 h after hospital admission result from uncontrolled hemorrhage. Physical trauma and hemorrhage are frequently associated with complex pathophysiological and immunological responses. To develop a greater understanding of the mechanisms of single and/or multiple trauma, reliable and reproducible animal models, fulfilling the ethical 3 R's criteria (Replacement, Reduction and Refinement), established by Russell and Burch in 'The Principles of Human Experimental Technique' (published 1959), are required. These should reflect both the complex pathophysiological and the immunological alterations induced by trauma, with the objective to translate the findings to the human situation, providing new clinical treatment approaches for patients affected by severe trauma. Small animal models are the most frequently used in trauma research. Rattus norvegicus was the first mammalian species domesticated for scientific research, dating back to 1830. To date, there exist numerous well-established procedures to mimic different forms of injury patterns in rats, animals that are uncomplicated in handling and housing. Nevertheless, there are some physiological and genetic differences between humans and rats, which should be carefully considered when rats are chosen as a model organism. The aim of this review is to illustrate the advantages as well as the disadvantages of rat models, which should be considered in trauma research when selecting an appropriate in vivo model. Being the most common and important models in trauma research, this review focuses on hemorrhagic shock, blunt chest trauma, bone fracture, skin and soft-tissue trauma, burns, traumatic brain injury and polytrauma.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Comparability; Polytrauma; Rat model; Translation pitfalls; Translational research; Trauma research